2015
DOI: 10.1002/hed.24012
|View full text |Cite
|
Sign up to set email alerts
|

Overt and occult vidian canal involvement in juvenile angiofibroma and its possible impact on recurrence

Abstract: Vidian canal involvement in juvenile angiofibroma is almost universal (14 of 16) and may be occult to CT evaluation. The site may harbor microscopic residual tumor after seemingly complete excision. Surgical attention toward it may reduce recurrences. © 2015 Wiley Periodicals, Inc. Head Neck 38: E421-425, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
11
1
1
Order By: Relevance
“…In detail, the pterygoid root is frequently involved by residual JA, a finding that led Howard et al to recommend extensive drilling of the basisphenoid to reduce the persistence rate . Indeed, the pterygoid root is considered to be the epicenter of the lesion growth from first branchial artery remnants that run through the vidian canal, which can frequently harbor lesion residues that can be overlooked during endoscopic surgery . In our series, all unintentional pJAs were located around the area of the pterygoid root even if extensive drilling of the basisphenoid adjacent to the lesion was always meticulously performed.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In detail, the pterygoid root is frequently involved by residual JA, a finding that led Howard et al to recommend extensive drilling of the basisphenoid to reduce the persistence rate . Indeed, the pterygoid root is considered to be the epicenter of the lesion growth from first branchial artery remnants that run through the vidian canal, which can frequently harbor lesion residues that can be overlooked during endoscopic surgery . In our series, all unintentional pJAs were located around the area of the pterygoid root even if extensive drilling of the basisphenoid adjacent to the lesion was always meticulously performed.…”
Section: Discussionmentioning
confidence: 60%
“…13 Indeed, the pterygoid root is considered to be the epicenter of the lesion growth from first branchial artery remnants that run through the vidian canal, which can frequently harbor lesion residues that can be overlooked during endoscopic surgery. 14,15 In our series, all unintentional pJAs were located around the area of the pterygoid root even if extensive drilling of the basisphenoid adjacent to the lesion was always meticulously performed. The pivotal role of the vidian canal in JA persistence was recently highlighted by Thakar et al in a series of 15 patients treated with endoscopic surgery.…”
Section: Unintentional Persistencementioning
confidence: 64%
See 1 more Smart Citation
“…Meticulous subperiosteal dissection and drilling of these areas assist in complete removal and avoiding recurrences . Thakar et al reported that involvement of the vidian canal is almost universal in juvenile angiofibroma and may not be detected on CT; this site may still harbor microscopic residual tumor after an apparently complete resection and should receive particular surgical attention to reduce the chances of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…These features contribute to microscopic residual disease and subsequent recurrences despite a seemingly complete tumor excision. Microscopic residual tumor is especially likely in the vidian canal-pterygoid complex [14].…”
Section: Discussionmentioning
confidence: 99%